2007
DOI: 10.1002/pon.1265
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and disability benefits: a synthesis of qualitative findings on advice and support

Abstract: Following the Supportive and Palliative Care Guidance, a call was made for a meta-ethnography on social support services for people affected by cancer. We responded by focusing on the topic of financial advice and support. After a scoping exercise revealed little qualitative evidence, we adopted the chief aim of identifying issues for research. Over 50 keywords relating to patient finances, cancer and qualitative research were entered into electronic search databases and combined. Because of the nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Additionally, the stronger correlation between SIS and psychological needs subscale of SCNS-SF34 was confirmed, while no correlations were found between the SIS and other subscales of support care needs. Our findings supported the view that suffering had been closely related to emotional distress [32]. As Wittmann [31] explains, “changes to the self resulting from the inability of a person’s attributes or coping mechanisms to adapt may lead to greater suffering.”…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the stronger correlation between SIS and psychological needs subscale of SCNS-SF34 was confirmed, while no correlations were found between the SIS and other subscales of support care needs. Our findings supported the view that suffering had been closely related to emotional distress [32]. As Wittmann [31] explains, “changes to the self resulting from the inability of a person’s attributes or coping mechanisms to adapt may lead to greater suffering.”…”
Section: Discussionsupporting
confidence: 88%
“…High costs of end of life care for the uninsured and underinsured in the US are well described in the literature [43,45,48,58,59]. Countries that have universal health coverage also identified financial burdens for the poor accessing end of life care services [5,17,[60][61][62]. Expenses included bridging costs of the gap payments and costs of services and goods exceeding those provided by a government health service.…”
Section: Affordabilitymentioning
confidence: 99%
“…To date, a small body of work in the UK has shown that financial worries can add to the stress of cancer diagnosis and treatment [3,4,40]. The findings of this study demonstrate why it is difficult for those affected by cancer to pursue benefit claims themselves, but that welfare rights services transform patients' experiences and provide access to much needed benefits.…”
Section: Discussionmentioning
confidence: 76%
“…Elements of more generic relevance beyond the UK may be the added burden resulting from the financial consequences of cancer diagnosis and treatment. Relating the findings to the limited available literature backs up existing research that individuals in the UK struggle with the benefits system when left to deal with it alone [40]. Furthermore, people affected by cancer in the UK miss out on benefits to which they are entitled in the absence of specialist services [3,4] and that there are considerable additional costs associated with cancer treatment [22].…”
Section: Discussionmentioning
confidence: 82%